(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Establishment of full enteral feed is a major challenge in the care of preterm low birth weight (LBW) neonates. Probiotics are live microbial supplements that colonize preterm bowel with favourable flora, improve tolerance to feed and promotes growth of these premies. Objective: To determine the effect of probiotic supplementation on feed tolerance, postnatal weight gain, duration of hospital stay in preterm low birth weight babies. Methods : This prospective clinical trial was conducted in the Neonatal Intensive Care Unit (NICU), Bangabandhu Sheikh Mujib Medical University, (BSMMU) from February, 2012 to November, 2012. A total of 65 preterm, low birth weight ( LBW) newborns were included in this study. A multistrain probiotic suspension was given once daily to the infants in probiotic group along with expressed breast milk (EBM) through the nasogastric tube/ dropper from the first day of feed which was continued till attainment of full feed. Those in controls received only expressed breast milk. Weight, feed volume increment, features of intolerance were followed up daily. Relevant investigations were done whenever indicated. Results: The mean time to reach full enteral feed in probiotic and control group was 13.71±3.4 vs 16.53±6.13; p<0.05. But weight gain was not affected by supplementation. Hospital stay was shorter in supplemented group. Conclusion: Probiotic supplementation in preterm low birth weight babies improves feed tolerance and decreases hospital stay but does not affect weight gain. Bangladesh J Child Health 2015; VOL 39 (2) :82-87